Automation and Electronic Control of Marine Gas Turbine Engine for Ship Revamp - Niculescu, Filip; Claudia Borzea,; Adrian Savescu,; Andrei Mitru,; Mirela Letitia Vasile, (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Gas turbines used in propulsion ensure increased efficiency and safety, with a very good power / weight ratio and with low maintenance and operation costs. Due to becoming out-of-date and reaching the maximum operation hours and expected lifetime, which can cause malfunctioning, older turbine engines on frigates need to be replaced with newer generation propulsion engines. The paper presents the replacement of the turbine engine on a defence frigate, focusing on the automation and electronic control solution employed for a propulsion turbine, integrating state-of-the-art techniques. The electronic system ensures control, monitoring and alarm functions, including overspeed protection. A local control panel interfacing the PLC displays the operating parameters and engine controls, also providing maintenance and calibration sequences. The proposed solution enables both the local and the remote control of the ship’s gas turbine.